Conceptual Overlapping Clustering for Effective Selection of Parental Rice Varieties - Dabbiru, Madhavi; Mogalla, Shashi; Rao, PRM (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The process of rice breeding involves producing new rice varieties as a cross of parental rice varieties followed by rigorous testing and examination phase for purity, productivity and resistivity to regional climatic conditions. The selection of appropriate parental seeds to produce new rice variety with more or less predictable characteristics is highly desirable as it reduces expensive experimental evaluation efforts. Authors suggest the applicability of Conceptual Overlapping Clustering Algorithm [7] developed by them for conceptual overlapping clustering to aid proper selection of rice varieties and demonstrated the performance of this algorithm on a real world dataset.